Periotest Evaluation of Stability after Insertion of Temporary Anchorage Device - Hussain Jabar Kadhem; Akram Fasial Alhuwaizi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Skeletal anchorage devices was developed for absolute anchorage during orthodontictreatment. Because of immediate loading on orthodontic miniscrews, early stability became a essentialrequirement for loading forces on miniscrews.Objective: The aim of this study was to evaluate the early stability of the miniscrews after two weeks ofinsertion and the effect of the length and the side of insertion of the miniscrews on its stability using Periotestdevice.Material and Method: Thirty- three orthodontic patients in a collage clinic were recruited who requiredbilateral miniscrews for orthodontic anchorage. Under local anesthesia, each patient received two miniscrewsin the maxillary buccal area (one side 1.6x8mm and the other side 1.6x10mm). after two week early stabilitymeasured using Periotest device.Results: There was no significant different in stability of miniscrew between right and lift sides and betweenshort and long miniscrews.Conclusion: length of miniscrew and side of insertion do not affect the early stability of miniscrew.